Effects of High Carbohydrate Diet-Modulated Microbiota on Gut Health in Chinese Perch - Zhang, Yanpeng; Liang, Xu-Fang; He, Shan; Chen, Xu; Wang, Jie; Li, Jiao; Zhu, Qiangsheng; Zhang, Zhen; Li, Lu; Alam, Muhammad Shoaib (Frontiers in Microbiology, 2020)
High carbohydrate diet-induced damage in gut is linked to changes in gut permeability and microbiota. However, the mechanisms of action are not clear, especially in non-mammals. We performed the gut microbiota profiling in Chinese perch fed with different content of starch diets (0%, 10%, 20%) by 16S rRNA sequencing. The gut permeability, metabolites, histological analysis, and inflammatory infiltration were evaluated. We found that gut microbial diversity, beneficial bacteria quantity, and lactic acid content were higher in C10 group than in the other groups. The lower level of gut microbial diversity was observed in C20 group, and mycoplasma was the overwhelmingly dominant species, but the butyric acid-producing bacteria and butyric acid level were significantly reduced. The gut permeability in C20 group was also increased due to the decreased mRNA expression levels of tight junction proteins caused by the butyric acid deficiency and gut lipid droplets accumulation. Then a large amount of LPS penetrated into the plasma, resulting in inflammation. These results suggested that high carbohydrate diet-induced damage in gut could be attributed to the endotoxemia, permeability, and gut microbiota, especially the role of mycoplasma and butyric acid-producing bacteria. In addition, predictive functional profiling of microbial communities by PICRUSt showed that C10 group enriched pathway related to membrane transport and down-regulated the pathways related to energy, coenzyme factor and vitamin metabolism, while C20 group exhibited reversed results. These data showed that the high-carbohydrate diet reversed the beneficial changes in gut microbial metabolism resulted from the medium-carbohydrate diet, and further demonstrated that microbiota played a key role in the gut damage caused by the high-carbohydrate diet. Our findings provide a reference for the targeted regulation of gut microbiota to mitigate the damage caused by the increase in starch content in fish feed (cost saving).